Design and Development of Electricity Use Management System of Surabaya State Shipping Polytechnic Based on Decision Tree Algorithm - Realdo, Adam Meredita; Nugraha, Anggara Trisna; Misra, Shubhrojit (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2021)
Electrical energy has become a primary need in society, including in education. This is related to the number of electrical equipment used to support teaching and learning activities. However, this is not directly proportional to the students' awareness of the importance of saving energy. From this, the authors create a management system for electric power, which aims to save electricity consumption by limiting the use of electrical loads. In this system, the method used is a decision tree; the goal is to limit and set priorities for electrical loads. When three classes are ON simultaneously, there will be a reduction in the electrical load. There is a website for monitoring and changing the automatic or manual mode in this system. The manual mode is used to control the electrical load according to the status entered on the website. While the automatic mode regulates the use of electrical loads by controlling the ON or OFF conditions using a schedule that has been made, the website also monitors current, voltage, power, energy, and usage costs. The system has been tested with automatic and manual modes for monitoring data on the website. It has data updates every 10 minutes. The system has also been tested by scheduling using a decision tree and compared with scheduling without using a decision tree. From the test results for a day, it can be concluded that the system created is able to save electricity consumption. This is reinforced by a decrease in energy use of 1,17 kWh and a cost of Rp. 1.116